The role of social-psychological factors of victimity on victimization of online fraud in China - Zhang, Zhi; Ye, Zhi (Frontiers in Psychology, 2022)
Introduction The high incidence of online fraud in China poses a great threat to the social stability and property security of society. Victimity is the state or mindset of victims, referring to the various conditions related to being victims of crimes. Examining the association between the inherent and extrinsic factors of victimity and victimization of online fraud is of great importance for revealing the psychological mechanism of victimization and drawing up preventative measures. Methods Through the questionnaire survey of 504 online fraud victims and 523 non-victims, univariate analysis and logistic regression analysis were used to investigate the risk factors correlated with victimization. Results Age, education, and social support are positively correlated with fraud victimization, while impulsiveness, trust tendency, smartphone usage, and negative life experiences are negatively correlated with fraud victimization. Subsequent regression analyses showed that all the factors above, except for smartphone usage, are significant predictors for online fraud victimization. Discussion Our conceptual model and empirical results demonstrate the important role of victimity in making an individual become a victim and help clarify the mixed findings of previous studies on the risk factors for online fraud.